The Effectiveness Of An Educational Program Based On Mednik Theory In Developing Communication Skills Among Students Of The Institute Of Fine Arts In The Subject Of Art Analysis And Criticism (Journal of the College of Basic Education, 2025)
The research aims to identify "the effectiveness of an educational program based on Mednik's theory in developing communication skills among students of the Institute of Fine Arts in the subject of art analysis and criticism", The current research community was determined by the students of the Institute of Fine Arts, Al-Rusafa I, Baghdad, numbering (176) students. A random sample was selected, which was represented by the students of the Department of Fine Arts, numbering (40) students. The students were distributed into two groups (control and experimental), with (20) students for each group. The researcher was keen to ensure that the two groups were equal in some variables, including: (chronological age, environment, intelligence, previous experience test, communication skills test), The researcher identified the topics of the educational material that he would study during the experiment period with eight topics. The researcher formulated (8) educational objectives and (20) behavioral objectives, and prepared teaching plans for them. Then he presented them to a group of arbitrators and specialists to judge their suitability. The necessary modifications were made to them and they became ready for application in light of their opinions, A research tool was designed, which was a skill test consisting of (4) items corrected by an observation card consisting of (20) items, with a five-point scale and a total score of (100) points, The apparent validity and reliability of the test were verified. The results showed the superiority of the experimental group that studied according to the educational program based on Mednik's theory over the control group that studied in the usual way, which led to the rejection of the null hypotheses of the research.